Everyday discourse as a space of citizenship. The linguistic construction of in-groups and out-groups in online discussion boards - Määttä Simo K.; Suomalainen Kaarit; Tuomarla Ulla (My University, 2022)
In this paper, we analyze online discussion threads related to national belonging in Finland, Denmark, and France. These discussions are all related to immigration and the definition of ‘legitimate’ citizens. Our approach is empirical: the goal is to show how in-groups and out-groups are construed linguistically and discursively in the data and how the interactants negotiate membership categories and express their opinions regarding them. The most important in-group in the datasets consists of the nationals born in the country, whereas the out-group par excellence is formed by Muslims. The data show how the boundaries of national communities are performatively constructed through the everyday discourse of online fora, which constitute an important arena of societal debate today. This discourse draws its force from the reiteration of stereotypical generalizations and the power attached to the written word in a communication environment enabling an efficient dissemination of ideological discourse.